Aditivos para hormigones, morteros y pastas - Gaspar Tebar, Demetrio (Materiales de Construcción, 1984)
This article comments on the increasing importance of the use of admixtures for concrete, mortars and grouts as well as the specific effects they produce, thus requiring a suitable Spanish Normative, whose performance was taken in charge by a Working Group of the Technical Commission n.° 83 from the IRANOR, created for this purpose.This article is first of a series which intends to give an account of the works, on the Normative of those additives, the Working Group is carrying out.